Visual Representation of Acehnese Traditional Music on Digital Media YouTube and TikTok: English - Berlian Denada; Asrinaldi Basrimba; Teuku Muhammad Husni (fakultas Desain Komunikasi Visual, 2026)
This study aims to analyze the revitalization of Acehnese traditional music through visual representation on digital platforms, particularly YouTube and TikTok. The rapid development of digital media has transformed the ways traditional music is produced, distributed, and consumed, especially among younger generations. This research employs a qualitative approach using visual analysis methods to examine selected Acehnese traditional music videos. Data were collected through screenshot techniques and analyzed based on visual composition, cultural costumes, environmental settings, performance movements, and production techniques. The findings reveal that the revitalization of Acehnese traditional music occurs not only in its musical elements but also through the adaptation of modern visual aesthetics. The use of cinematic composition, overlay techniques, representations of Acehnese coastal landscapes, and dominant cultural symbols such as traditional costumes and properties indicate a negotiation between tradition and modernity within digital spaces. Furthermore, the active participation of young performers demonstrates that digital platforms function as dynamic media for cultural transmission. This study concludes that YouTube and TikTok serve as strategic spaces for strengthening Acehnese cultural identity through the visual construction of traditional music, thereby supporting cultural preservation and revitalization in the digital era.